Pelatihan Digital Marketing dan Formulasi Sabun dari Minyak Kelapa di Sentra Industri Pengolahan Kelapa Lombok Utara - Yuliana, Ika; Ramandha, Muhammad Eka Putra; Pratiwi, Baiq Yulia Hasni (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This service aims to increase Sentra Industri Pengolahan Kelapa knowledge and skill about soap formulation from coconut oil, thus they could produce a good quality coconut oil soap. Also, this act aims to educate them how to sell their product via social media such as Instagram, Tiktok, etc. Research methodology: This service was conducted at Sentra Industri Pengolahan Kelapa, Kab. Lombok Utara, NTB and attended by 30 participants. It was consist of two main event: (1) Education and training of coconut oil soap formulation and (2) Education and training of social media used for digital marketing. The understanding of audience was measured using pre-test and post-test questionnaire. The data was analyzed using SPSS 27. Results: According to questionnaire collected, there are significant increase of audience knowledge regarding soap formulation and the use of social media for digital marketing after training. Conclusions: In short, the service has a significant impact on Sentra Industri Pengolahan Kelapa’s knowledge and skill in formulating a good quality coconut oil soap. Moreover, Sentra Industri Pengolahan Kelapa could start sell their product via social media created. Limitations: Large-scale production and marketing of the soap product are required to be able to measure the profit increase of Sentra Industri Pengolahan Kelapa. Contribution: This training would benefit the small and medium enterprises (SMEs) to make a standarized coconut oil soap and take advantage of social media to sell their product. Therefore, this would increase omzet of Sentra Industri Pengolahan Kelapa and eventually improving the economy of Kab. Lombok Utara.